Peran Kepala Sekolah Perempuan Dalam Meningkatkan Mutu Sekolah: Sebuah Tinjauan Literatur - Fadli Firdaus (Departement of Mathematics Education, 2023)
This study aims to examine the role of female school principals in improving the quality and quality of schools. So far it is known that many women occupy these positions. The role of women in leadership is always juxtaposed with male leadership. In this study, researchers used a literature approach by gathering various sources from national and international articles and other sources related to women's leadership. The results of this study conclude that women's leadership has a very vital role in improving the quality and progress of the organization they lead. Almost all organizations that employ women as leaders have succeeded in becoming advanced and well-developed organizations. The typical female leadership style is able to change a bad organizational culture for the better. Therefore, in the future women can be the main choice in leadership and side by side with men.